Webinar dan Workshop Pemanfaatan Aplikasi Pembelajaran Daring di Masa Pandemi Covid-19 Pada MGMP PPKn Kabupaten Garut - Ade Suherman; Tetep Tetep; Jamilah Jamilah; Odang Hermanto; Yuyun Susanti (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2020)
The Covid-19 virus pandemic changes the pattern of several activities, one of which is learning from face-to-face (conventional) to online or online learning. Online learning is an alternative in overcoming this problem. The purpose of this service is to improve teacher competence in the use of online learning applications during the Covid-19 pandemic at the MGMP PPKn Garut Regency. The research subjects were PPKn teachers, especially those in Garut Regency and generally throughout Indonesia because the national workshop participants were open to the public. Virtual webinars and workshops with the zoom meeting application. The results obtained from these activities are: 1) Motivation of the teacher in online learning so that teaching and learning activities run optimally and can practice several applications that support online learning such as; Mentimeter application, google classroom, zoom meeting, google meet, schoology, modle, yutube, ig, whatapps group, and email; (2) Online learning has flexibility in its implementation and is able to encourage independent learning and motivation to be more active in learning; (3) online learning encourages the emergence of social distancing behavior and minimizes the emergence of a crowd of students so that it is considered to reduce the potential for the spread of Covid-19 in the school environment